Perceptions of Water Services and Innovations to Improve Water Services in Tanzania. (July 2019) - Sherry, Julia; Juran, Luke; Kolivras, Korine N.; Krometis, Leigh-Anne H.; Ling, Erin J.
This study examines user perceptions of existing water services and proposed prepaid water meter and solar power innovations to improve water services in Tanzania. Based on 14 key informant interviews and six focus group discussions that included 61 participants, data from three rural and three urban study sites reveal that existing water services are generally perceived as poor, and the proposed prepayment and solar innovations offer benefits including increased transparency, accountability, and convenience. However, users also perceived challenges with the proposed innovations, including disenfranchisement of vulnerable populations and technical difficulties. The Government of Tanzania may implement the prepaid water meter and solar power technologies in the near future. Thus, it is critical to incorporate user perceptions on the acceptability, feasibility, and scalability of such technologies prior to large-scale implementation.